Die gewinnende Kraft des Guten: Ansatz einer evangelischen Ethik - Härle, Wilfried (Theologische Literaturzeitung, 2004)
The interplay of virtue, duty, and goodness plays a dominant role in the history of ethics. Following Schleiermacher, it can be shown that this is not a matter of opposites, but rather a pattern of three related aspects of fully worked out ethics. -- This essay attempts to show how such an integrated ethics can be described and typified. The author proposes the idea of a "model ethics", and outlines the changes in language, normative function, and tasks that it implies. This essay also emphasizes the basic difference between a teleologically and a consecutively motivated ethos.